The effect of Phyllanthus emblica (Amla) fruit supplementation on the rumen microbiota and its correlation with rumen fermentation in dairy cows - Tilahun, Mekonnen; Ma, Lu; Callaway, Todd R.; Xu, Jianchu; Bu, Dengpan (Frontiers in Microbiology, 2024)
Medicinal plants have many potential benefits enhancing productivity, quality, and animal health, which have been heavily explored recently. Amla fruit is rich in beneficial phytochemicals like phenolic acids, flavonoids, tannins, alkaloids, glycosides, and terpenoids. This study investigated the impact of fresh Amla fruit on ruminal microbial composition and its correlation with rumen fermentation endproducts in lactating dairy cows. The study employed a repeated crossover design involving eight ruminally cannulated mid-lactation Holstein dairy cows. The cows received fresh Amla fruit at four levels (0, 200, 400, and 600 g/d). The results showed that administering 400 g/d of fresh Amla fruit (FAF) supplementation increased the relative abundance of Firmicutes (p = 0.02). Conversely, at 200 g/d FAF supplementation, the relative abundance of ruminal Bacteroidota was higher than the 0 and 400 g/d FAF supplementation (p < 0.01). Linear discriminant analysis effect size was used to identify the most differentially abundant bacterial taxa in the 200, 400, and 600 g/d FAF group, which were: Clostridia vadinBB60 group, Oscillospiraceae, and Elusimicrobium, respectively. The random forest species abundance statistics identified Oscillospiraceae V9D2013 as a biomarker related to milk yield.Oscillospiraceae, Bacilli RF39, norank_f Prevotellaceae, and Bifidobacterium were positively correlated with ruminal total VFA and molar proportion of propionate, while Rikenellaceae RC9 gut group and Clostridia vadinBB60 were negatively correlated. Overall, FAF supplementation affected the abundance of beneficial microbes in a dose-dependent manner, which can improve milk yield, efficiency, rumen health, desirable fatty acids, and animal health.